Winter is coming: Wintertime mindset and wellbeing in Norway - Leibowitz, Kari; Vittersø, Joar (International Journal of Wellbeing, 2020)
Previous research of the effect of winter on wellbeing has yielded contradictory findings. While there is evidence that the lack of sunlight in wintertime can lead to seasonal depression and negative emotions, many individuals are able to thrive during the winter. What might determine whether the darkness of winter leads to poor psychological outcomes? To investigate whether or not mindset contributes to wintertime wellbeing, we assessed wintertime mindset via a Wintertime Mindset Scale measuring attitudes towards winter. A survey of 238 respondents from southern Norway, northern Norway, and the Arctic island of Svalbard identified correlations between positive wintertime mindset and measures of wellbeing, including life satisfaction and positive emotions. Latitude and wintertime mindset were also correlated, with more northern residents, who experience significantly more darkness and somewhat colder temperatures during the winter, holding more positive wintertime mindsets, and wintertime mindset statistically mediating the relationship between location and wellbeing. These results suggest that mindset is a previously overlooked factor of seasonal wellbeing, especially in places where the winter darkness is more extreme. Implications of these findings and suggestions for further research are discussed.